Blood Eosinophils Subtypes and Their Survivability in Asthma Patients - Januskevicius, Andrius; Jurkeviciute, Egle; Janulaityte, Ieva; Kalinauskaite-Zukauske, Virginija; Miliauskas, Skaidrius; Malakauskas, Kestutis (Cells (Basel, Switzerland), 2020)
Eosinophils subtypes as lung-resident (rEOS) and inflammatory (iEOS) eosinophils are different in surface protein expression, functions, response to IL-5 and localization in lungs. rEOS- and iEOS-like eosinophils are found in blood; thus, we aimed to investigate their quantity and survivability in asthma patients. A total of 40 individuals were included: 10 steroid-free non-severe allergic asthma (AA), and 18 severe non-allergic eosinophilic asthma (SNEA) patients, the control group consisted of 12 healthy non-smoking subjects (HS). A bronchial challenge with Dermatophagoides pteronysinnus allergen was performed for AA patients and HS. Blood eosinophils subtyping was completed with magnetic beads’ conjugated antibodies against surface CD62L. Eosinophils adhesion to hTERT airway smooth muscle (ASM) cells was measured by evaluating their peroxidase activity and viability by annexin V and propidium iodide staining. We found that the predominant blood eosinophil subtype in AA patients was iEOS, while rEOS prevailed in SNEA patients (p < 0.05). Moreover, rEOS demonstrated higher adhesion intensity compared with iEOS in all investigated groups. Both eosinophils subtypes of SNEA patients had higher survivability over the AA group. However, iEOS survivability from AA and SNEA groups was higher compared with rEOS under standard conditions, when rEOS survivability increased after their incubation with ASM cells. Bronchial allergen challenge abolished the dominance of blood iEOS in AA patients and prolonged only iEOS survivability. Though the challenge did not affect the adhesion of any eosinophils subtypes, the direct dependence of rEOS and iEOS survivability on their interaction with ASM cells was revealed (p < 0.05). These findings provide the premise for eosinophils subtype-oriented asthma treatment.